2008
DOI: 10.1021/bi7017865
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Monothiol Glutaredoxins from Saccharomyces cerevisiae Provide Further Insight into Iron-Sulfur Cluster Binding, Oligomerization, and Enzymatic Activity of Glutaredoxins

Abstract: Two novel monothiol glutaredoxins from yeast (ScGrx6 and ScGrx7) were identified and analyzed in vitro. Both proteins are highly suited to study structure-function relationships of glutaredoxin subclasses because they differ from all monothiol glutaredoxins investigated so far and share features with dithiol glutaredoxins. ScGrx6 and ScGrx7 are, for example, the first monothiol glutaredoxins showing an activity in the standard glutaredoxin transhydrogenase assay with glutathione and bis-(2-hydroxyethyl)-disulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
159
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(171 citation statements)
references
References 32 publications
11
159
1
Order By: Relevance
“…Glutaredoxins are widely considered the primary cellular catalysts for protein deglutathionylation (43,44). Notably, two glutaredoxins (Grx6 and Grx7) localize to the ER/Golgi region in yeast, and these enzymes have the potential to facilitate deglutathionylation of BiP (32,45). However, our preliminary data show no change in the kinetics of BiP-glutathione adduct reduction in the glutaredoxin-deficient grx6⌬ grx7⌬ strain (data not shown).…”
Section: Discussionmentioning
confidence: 72%
“…Glutaredoxins are widely considered the primary cellular catalysts for protein deglutathionylation (43,44). Notably, two glutaredoxins (Grx6 and Grx7) localize to the ER/Golgi region in yeast, and these enzymes have the potential to facilitate deglutathionylation of BiP (32,45). However, our preliminary data show no change in the kinetics of BiP-glutathione adduct reduction in the glutaredoxin-deficient grx6⌬ grx7⌬ strain (data not shown).…”
Section: Discussionmentioning
confidence: 72%
“…Iron-Sulfur Cluster Assembly-Another important point is that human Grx2 (SCSYC active site), poplar GrxC1 (YCGYC), S. cerevisiae Grx6 (TCSYS), and Trypanosoma brucei Grx1 (MCAYS) are able to bind an iron-sulfur cluster, most likely a [2Fe-2S] cluster (20,35,44,45). The crystal structures of Grx2 and GrxC1 in the holoform are similar and showed that the incorporation of the cluster requires the dimerization of the Grx and the presence of two external glutathione molecules (20,35,46).…”
Section: Role Of Grxs12 Active Site Organization For Regenerationmentioning
confidence: 99%
“…With few exceptions, such as yeast Grx 6 (54,59) and trypanosomal 1-C-Grx1 (16, 27, Fleitas, Manta, and Comini, unpublished), 1-C-Grxs are monomeric proteins in the apo-state (13,18,25,28,47,59,69,82). Similarly to 2-C-Grxs, distinct isoforms of 1-C-Grxs are found in the cytosol, nucleus, mitochondria as well as plant chloroplast (reviewed in 86).…”
Section: Fig 2 Sequence Analysis Of Monothiol Glutaredoxins (A)mentioning
confidence: 99%
“…Similarly to 2-C-Grxs, distinct isoforms of 1-C-Grxs are found in the cytosol, nucleus, mitochondria as well as plant chloroplast (reviewed in 86). Except for yeast Grx6 and Grx7 (59,60), most 1-C-Grxs lack or have negligible classical disulfide reductase activity (18,26,27,43,69,82). Instead, the capability to coordinate ISCs appears to be a common feature for 1-C-Grxs (16,40,42,43,54,67,89) with yeast Grx7 being, so far, the only known exception (59,60).…”
Section: Fig 2 Sequence Analysis Of Monothiol Glutaredoxins (A)mentioning
confidence: 99%
See 1 more Smart Citation